The Covid -19 Impact on the Capitalization of Indonesian Sharia Capital Market - Nengsih, Ifelda; Rahmi, Mega (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
The purpose of this study is to see whether Covid 19 pandemic affects stocks listed on the Jakarta Islamic Index (JII) in Indonesia. This study uses data time series as seen from the combined Islamic stock price index in JII from July 2019 to July 2020. In testing the hypothesis, the independent sample t-test and Mann Whitney test are applied to prove the effects of the Covid 19 pandemic on the Jakarta Islamic Index. The results showed that there is an impact of the Covid 19 pandemic on JII. A significance value of 0.000 evidence this 0.05 on the independent sample t-test and 0.004 0.05 on the Mann Whitney test. This means that during the covid 19 periods, the JII Index was under pressure compared to conditions before covid 19.